2017
DOI: 10.1080/10245332.2017.1402455
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1 and CXCL12 modulate proliferation and chemotherapy sensitivity of acute myeloid leukemia cells co-cultured with multipotent mesenchymal stromal cells

Abstract: These findings suggest a strong supporting affinity between MSCs and AML cells within the leukemic niche, where TGF-β1 and CXCL12 pathways play an important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 30 publications
0
31
1
Order By: Relevance
“…Nevertheless, it has been demonstrated that the activation of TGF‐β‐Smad3 signaling reduces acute myeloid leukemia cells proliferation by causing cell cycle arrest at G 1 phase . Moreover, TGF‐β1 inhibition enhances acute myeloid cell proliferation in co‐culture with BM‐MSC .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, it has been demonstrated that the activation of TGF‐β‐Smad3 signaling reduces acute myeloid leukemia cells proliferation by causing cell cycle arrest at G 1 phase . Moreover, TGF‐β1 inhibition enhances acute myeloid cell proliferation in co‐culture with BM‐MSC .…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 and SDF-1 blockades in animal models culminates in a remarkable decrease in the migration potential and the migration rate of transplanted stem cells to sites of demyelination, suggesting that the SDF-1/CXCR4 signaling pathway is critical for effective stem cell therapy [62]. Moreover, simultaneous blocking of both CXCR4 and transforming growth factor (TGF)-β receptor demonstrated that CXCR4 is necessary for colonization of MSCs in tumors, differentiation to myofibroblasts, and MSC survival [63,64]. MSCs express several chemokine receptors, including CXCR1, CXCR3, CXCR4, CXCR5, CXCR6, CCR1, CCR2, CCR3, CCR4, CCR5, and CCR9 [65].…”
Section: Colonization and Migration Of Mscsmentioning
confidence: 99%
“…As the interaction of leukemia cells with bone marrow stromal cells has impact on their biology and response to therapy and can modify the phenotype of stromal cells , it is of particular importance to verify the drugs efficiency in a bone marrow mimicking conditions. Most of the co‐culture studies concentrate on the stroma‐mediated effects on leukemia cells . However, it is also very important to monitor the vital state of stromal cells, as they are a source of protective and proleukemic signals.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to mimic the bone marrow conditions, multiple studies of protective role of the bone marrow stroma utilize in vitro co‐culture of human stromal and leukemia cells. The simplistic model of 2D co‐culture, even if does not contain all types of bone marrow niche components, is sufficient for initial screening of anti‐ or proleukemic factors and is broadly used in in vitro studies . Even if the cross‐talk between leukemia and stromal cells leads to a rearrangement of cells’ functions, it is still crucial to control and monitor the fundamental cellular processes and basal vital parameters of stromal cells.…”
mentioning
confidence: 99%